Machinations of spiritual entities in some of Charles Mungoshi’s works in English - Manyarara, Barbra Chiyedza (Journal for Studies in Humanities and Social Sciences, 2019)
Through a textual analysis methodology of three selected texts by Charles Mungoshi, the interactions between the spirit world and ordinary Shona people are examined to unlock some of the multiple meanings to be found in these cultural artefacts. Christian values are shown as largely in conflict against the Shona spiritual world with its tendency towards the supernatural. In the selected works, the ngozi spirit has a strong presence that controls the literary lives of the persons of these works. Although the ngozi spirit affects both young and old, males and females, its influence is felt the most by young girls, single women and other females in their families. The impact on the male species seems rather minimal, perhaps reflective of patriarchal order. In Shona cosmology there is a strong belief that the panacea for ngozi is atonement. This study, therefore, explores the workings of spiritual entities in the selected works.